Species delimitation methods reveal cryptic diversity in the Hypnea cornuta complex (Cystocloniaceae, Rhodophyta). Issue 2 (3rd April 2019) - de Jesus, Priscila Barreto; Costa, Adriele Leite; Nunes, José Marcos de Castro; Manghisi, Antonio; Genovese, Giuseppa; Morabito, Marina; Schnadelbach, Alessandra Selbach
ABSTRACT: The simple and convergent morphologies of many red algae make these species difficult to identify using traditional morphological characters. Many cryptic species have been described in recent years based on molecular datasets, and this has led to the application of an integrative taxonomy approach in species delimitation. Here, we performed several species delimitation methods (mBGD, ABGD, SPN, PTP, GMYCs and GMYCm) based on two different loci (COI-5P and rbc L) in species of the Hypnea cornuta complex. These methods were combined with morphological and phylogenetic data, extensive sampling, analysis of topotype material, and historically relevant herbarium samples. Our findings demonstrate that the groups morphologically assigned to H. cornuta and H. stellulifera consist of five different cryptic species. H. cornuta is a polyphyletic taxon composed of three well-separated lineages, thus requiring sequencing of type or topotype specimens to determine which one is Hypnea cornuta sensu stricto . We have revealed that the distribution of H. stellulifera is limited to Asia, while the Brazilian specimens initially assigned to this species were clarified as a new endemic species: Hypnea cryptica sp. nov. Our results indicated that only an integrative approach combining several lines of evidence, including morphology, nomenclature history, molecular data, biogeography and ecology can correctly solve the taxonomic status of widely distributed cryptic species.